Characterization of polypropylene (PP) and poly(ethylene terephthalate) (PET) multifilament braided textile structures for Achilles tendon partial substitution. (February 2021) - Morais, D.S.; Cruz, J.; Fangueiro, R.; Lopes, M.A.; Guedes, R.M.
Abstract: When tendon injuries present a too large damage extension, the conventional treatment options do not result, so a new prosthetic device needs to be developed to partially replace a tendon. Therefore, in this study, different braided textile structures based on polypropylene (PP) and poly (ethylene terephthalate) (PET) multifilament yarns were developed, using a textile technology-based technique, in order to mimic the fibrous structure of tendons. Structures with different architectures were developed using different PP or PET yarns number and different braiding take-up rates, which consequently leads to different braid angles. The braids architecture influenced the porosity level, swelling profile, wicking ability and mostly their mechanical behavior. It was observed that the load at failure of the braids was mainly controlled by the number of yarns, but the strain level was mostly influenced by the take-up rate and consequently by the braid angle. Regarding the stiffness level, it results from a combination of the yarns number and braid angle. The structure based on 16 PET yarns, produced with the highest take-up rate, revealed a very promising creep and force-relaxation behavior for the final application, as well as a very interesting fatigue resistance. Highlights: Different braided textile structures based on PP and PET multifilament yarns were developed. Using a textile technology-based technique, we mimic the fibrous structure of tendons. The braids architecture define their physical and mechanical behavior and the intrinsic physical properties of the yarns that compose them. Number of structure yarns and the braiding take-up rate are the main parameters adjustable to construct structures with different architectures. The PET_16 YH structure revealed a promising creep and force-relaxation behavior for the final application and a very good fatigue resistance.